Super-lift DC/DC converters - Ajay Kumar Sridhar (2011)
With DC transmitted at higher voltages over long distances proving to be cheaper than AC transmission, research in finding newer ways of increasing the DC voltage at lesser cost and higher efficiency has been of high priority in this era. Keeping in mind the performance of non-linear elements and the potential of power electronic devices in delivering output as desired the scope of research has been widening very broadly and will continue to do so. Also maintaining the output of the converter at the desired level irrespective of changes in load and input supply has been of high importance considering the regularity of such occurrences. This research starts with the introduction and study of Super-Life LUO Converters and its advantages over other Voltager Lift Techniques. These Super-Lift LUO converters have the distinct advantage of delivering high voltage output at better efficiencies and lesser ripple voltage. They also seem to improve the gain of the each stage exponetially. Further a controller is developed for controlling the output of the converters so that the output is maintained constantly irrespective of changes in input voltage and also changes in load. This helps in providing a constant output to the load so that its operation is not affected. The output voltage is inverted to AC voltage in order to make this converter applicable in day to day lives for usage with the normal components. An application wherein the usage of traditional converters and AC transformers is currently in use is chosen and this Super-Lift converter is substituted. This is a proposal could be carried out in the near future.